2011
DOI: 10.1002/ceat.201100160
|View full text |Cite
|
Sign up to set email alerts
|

Cold Flow Model Study of an Oxyfuel Combustion Pilot Plant

Abstract: The fluid-dynamic behavior of a circulating fluidized bed pilot plant for oxyfuel combustion was studied in a cold flow model, down-scaled using Glicksman's criteria. Pressures along the unit and the global circulation rate were used for characterization. The analysis of five operating parameters and their influence on the system was carried out; namely, total solids inventory and the air velocity of primary, secondary, loop seal and support fluidizations. The cold flow model study shows that the reactor desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…U j is the jet initial velocity, and Φ j is the passive scalar concentration at the jet inlet, which was defined as 1 in the mass fraction form in this work. e decay rates of the mean streamwise velocity 1/B and the scalar concentration 1/B Φ are calculated by the curve fitting the time-averaged data from simulation results based on Equations (12) and (13). For validation, data from 30 to 50 D j were used for calculation in order to be consistent with Larsson et al [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…U j is the jet initial velocity, and Φ j is the passive scalar concentration at the jet inlet, which was defined as 1 in the mass fraction form in this work. e decay rates of the mean streamwise velocity 1/B and the scalar concentration 1/B Φ are calculated by the curve fitting the time-averaged data from simulation results based on Equations (12) and (13). For validation, data from 30 to 50 D j were used for calculation in order to be consistent with Larsson et al [8].…”
Section: Resultsmentioning
confidence: 99%
“…e early measurement by Glass and Bilger [12] indicated that a turbulent jet flame (or as they called "a heated jet-wake") and an isothermal turbulent round jet (isothermal jet-wake) have very similar turbulence quantities, such as the turbulence intensities and shear stress. Cold models provide an easy way to investigate the influence of different variables and facilitate measurements for validation [13]. is and the fact that the results can be compared to experiments, and previous simulations validate further studies on the simplified case in [2][3][4][5][6] now with focus on the jet development as a function of position and Reynolds number (Re).…”
Section: Introductionmentioning
confidence: 99%
“…The tanks‐in‐series (TIS) model with the gamma extension model was used to model the RTD of the solids. The TIS model was used successfully in previous RTD studies of fluidized beds . It assumes that the system of interest consists of N statistically independent tanks of equal volume in series and that the solids in each tank are perfectly mixed.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…Several studies were carried out to optimize the operating parameters or investigate the flow behavior in industrial reactors 1, 3–10. Model simulation studies were also performed to identify the deviation from ideal reactors for these industrial RTD experiments.…”
Section: Introductionmentioning
confidence: 99%